Pattern and Characteristics of Violent Asphyxial Deaths: A Prospective Study from Belagavi Region - Gopal Govind Hargi; K.S. Gurudut; Jagadish Rao Padubidri; Pavanchand Shetty H.; Bhoopendra Singh (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Violent asphyxial deaths constitute a major proportion of medicolegal fatalities in India, with hanging and drowning being the most common mechanisms. Regional epidemiological data are essential for forensic interpretation and prevention strategies. Aim: To study the pattern and characteristics of violent asphyxial deaths in the Belagavi region with respect to demographic, environmental, and socio-economic factors, and to evaluate the effects of neck constriction in different forms of asphyxia. Materials and Methods: A prospective autopsy-based study was conducted over 18 months (November 2012–April 2014) at the Department of Forensic Medicine and Toxicology, Belagavi Institute of Medical Sciences, Karnataka. Out of 1,176 medico-legal autopsies, 175 cases of violent asphyxial deaths were included. Data regarding age, sex, marital status, residence, season, motive, manner of death, and type of asphyxia were collected from police records, circumstantial history, and detailed postmortem examination. Statistical analysis was performed using descriptive statistics and chi-square test. Results: Violent asphyxia constituted 14.88% of all autopsies. Hanging (62.28%) was the most common type, followed by drowning (28.57%). Suicidal deaths predominated (78.86%). Males were more commonly affected (73.71%), with the highest incidence in the 21–30 year age group. Married individuals and rural residents constituted the majority. A signi𿿿cant seasonal variation was observed, with maximum cases during summer. Hyoid bone fracture was noted in 20% of cases. Conclusion: Hanging and drowning remain the predominant modes of violent asphyxial deaths, mainly suicidal in nature, affecting young adult males from rural and socio-economically stressed backgrounds.